Fischer-Tropsch Synthesis over Unpromoted Co/ɣ-Al2O3 Catalyst: Effect of Activation with CO Compared to H2 on Catalyst Performance - Phathutshedzo Rodney Khangale; Reinout Meijboom; Kalala Jalama (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The effect of activating Co/Al2O3 catalyst by diluted CO or H2 on catalyst performance for Fischer-Tropsch reaction was investigated. The catalyst was prepared by incipient wetness impregnation of the support and characterized using BET N2 physisorption, SEM, and XRD analyses. The reduction behavior of the catalyst in presence of CO and H2 individually was evaluated using TPR analyses. The data reveal that CO activates Co/Al2O3 catalyst at a lower temperature than H2 and produces a catalyst with higher rate for liquid product formation. It also leads to higher methane selectivity probably due to some cobalt carbide formation.